Remote and local ischemic preconditioning increases isometric strength and muscular endurance in recrea-tional trained individuals - Luiz Guilherme da Silva Telles; Luís Leitão; Gleisson da Silva Araújo; Rhodes Serra; Christian Geórgea Spithourakis Junqueira; Aline Aparecida de Souza Ribeiro; Michelle de Souza Ribeiro; Estêvão Rios Monteiro; Jeferson Macedo Vianna; Jefferson da Silva Novaes (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The aim of the present study was to verify the acute effect of remote and local IPC application before isometric strength, lumbar and lower limbs manual grip, and upper limbs and trunk muscle endurance tests in recreationally trained individuals. The volunteers were 22 men (age: 26.2 ± 6.9 years, weight: 83.4 ± 11.6 kg, height: 175.4 ± 5.8 cm, BMI: 27.1 ± 3.5 kg.m-2) recreationally trained (4.6 ± 3.3 years) in resistance exercise (RE) that performed three visits on non-consecutive days (three to seven days apart). This was a crossover and randomized study. In the first visit, the Informed Consent Form (ICF) was signed, according to the Declaration of Helsinki, and the PAR-Q was completed. Immediately after, anthropometrics was assessed, followed by familiarization with the tests. At the second and third visits, the volunteers were randomly assigning to the following experimental protocols: a) IPC protocol with 220 mmHg + isometric strength and muscular endurance tests (IPC); or b) control protocol (CON) isometric strength and muscular endurance tests. Isometric handgrip strength was significantly higher in IPC compared to CON (61.59±10.18 vs. 58.95±10.84, 4.47Δ%, p=0.01). Lumbar isometric strength was significantly higher in IPC compared to CON (165.36±22.56 vs. 156.77±22.81, 5.48Δ%, p= 0.01) and lower limbs isometric strength was significantly higher in IPC compared to CON (163.09±22.92 vs. 154.86±21.55, 5.31Δ%, p=0.01). Push-up repetitions were significantly higher in IPC compared to CON (43±12.80 vs. 38.91±13.03,10.51Δ%, p=0.01). The trunk flexion repetitions were significantly higher in the IPC compared to the CON (46.05±13.28 vs. 40.23±11.18, 14.46Δ%, p=0.01). In conclusion, local IPC significantly increased upper limb isometric strength and muscle endurance compared to the control protocol. Remotely, IPC significantly increased lower limb isometric strength, lumbar and trunk flexion muscular endurance compared to the control protocol.